Benzoic acid supplementation improves the growth performance, nutrient digestibility and nitrogen metabolism of weaned lambs - Zhang, Wenjie; Sun, Shuo; Zhang, Yaqian; Zhang, Yanan; Wang, Jianguo; Liu, Zhiqiang; Yang, Kailun (Frontiers in Veterinary Science, 2024)
The purpose of this experiment was to explore effects of benzoic acid supplementation on growth performance, nutrient digestibility, nitrogen metabolism and plasma parameters of weaned lambs. A total of 40 weaned male Hu sheep lambs with similar body weight were randomly divided into 4 groups: control with no benzoic acid (0 BA) and the lambs in other 3 groups were fed 0.5%, 1% and 1.5% benzoic acid on the basis of experimental diet (0.5 BA, 1 BA and 1.5 BA, respectively). The experiment lasted for 60 days. Results showed that the average daily gain of 1 BA group was significantly increased (p < 0.05) when compared to 0 BA and 1.5 BA groups, while an opposite tendency of dry matter intake to average daily gain ratio was observed. The dry matter, organic matter, neutral detergent fiber and acid detergent fiber digestibility of 1 BA group was significantly increased (p < 0.05) as compared with 0 BA and 1.5 BA groups as well as plasma albumin content. Also, the urinary hippuric acid and hippurate nitrogen concentrations in 1 BA and 1.5 BA groups were higher (p < 0.05) than those in 0 BA and 0.5 BA groups. Additionally, the nitrogen intake in 0.5 BA and 1 BA groups was significantly increased (p < 0.05) when compared to other groups. At 1 h after morning feeding, the plasma benzoic acid concentration of 1 BA group reached up to maximum value and was higher (p < 0.05) than other groups, and then began to decrease. Similarly, the hippuric acid concentration in plasma of 1 BA and 1.5 BA groups was higher (p < 0.05) than that of 0 BA group from 1 h to 4 h post morning feeding. At 3 h after feeding, the urea nitrogen concentration in plasma of 0 BA group was higher (p < 0.05) than that of 1.5 BA group.Overall, the appropriate supplementation of benzoic acid (1%) in the diet can improve growth performance and nitrogen metabolism of weaned lambs.